Investigating scalar-tensor gravity with statistics of the cosmic large-scale structure - Reischke, Robert; Spurio Mancini, Alessio; Schäfer, Björn Malte; Merkel, Philipp M. (Monthly notices of the Royal Astronomical Society, 2019)
ABSTRACT. Future observations of the large-scale structure have the potential to investigate cosmological models with a high degree of complexity, including th